2009
DOI: 10.3233/ica-2009-0302
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy logic based efficient energy saving approach for domestic heating systems

Abstract: This paper focuses on the designing of an energy saving method for a domestic heating system based on electrical heaters. A multi-agent system architecture with two fuzzy rule based systems has been used: a fuzzy model, to estimate the energy requirements and a fuzzy controller, to distribute the energy to all of the installed heaters. The aim is to reduce the energy spent for heating the house while maintaining the predefined comfort level. The proposal has proved valid in realistic simulations, although some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 16 publications
(15 reference statements)
0
27
0
Order By: Relevance
“…For example, factors such as whether the household comprises only one person or a family of several people; factors determining whether a building is green, such as the building design, building exterior [48], ventilation design [49,50], green roofs [51,52], and the facilities and materials used; and factors regarding the different daily energy consumption or conservation habits of each member of a household, such as using natural light, energy-conserving lamps [53][54][55], ventilation equipment [56], air conditioning [57], heating systems [58], solar energy [59], water-or electricity-conserving equipment, the type and number of vehicles, and the planting of green plants. Because of the varying impact, we first used Delphi expert assistance to select and archive criteria for this study, and confirmed the AHP hierarchical framework for each criterion, as shown in Figure 4.…”
Section: Application Of Ahp and Utility Theory To Examine X 1 Criterimentioning
confidence: 99%
“…For example, factors such as whether the household comprises only one person or a family of several people; factors determining whether a building is green, such as the building design, building exterior [48], ventilation design [49,50], green roofs [51,52], and the facilities and materials used; and factors regarding the different daily energy consumption or conservation habits of each member of a household, such as using natural light, energy-conserving lamps [53][54][55], ventilation equipment [56], air conditioning [57], heating systems [58], solar energy [59], water-or electricity-conserving equipment, the type and number of vehicles, and the planting of green plants. Because of the varying impact, we first used Delphi expert assistance to select and archive criteria for this study, and confirmed the AHP hierarchical framework for each criterion, as shown in Figure 4.…”
Section: Application Of Ahp and Utility Theory To Examine X 1 Criterimentioning
confidence: 99%
“…For example, the building envelope could help in reducing the heating losses. The building topologies have been extracted from the analysis of the building market, and have been reported in [13,16]. The proposed building topologies should be used to validate any proposal of an electrical energy distribution for electrical heating systems.…”
Section: Preliminariesmentioning
confidence: 99%
“…In previous works, the development of such a device has been analyzed, and a multi agent hybrid fuzzy system has been proposed [15,14,16,13]. The solution integrates the electric heaters and the CCU.…”
Section: Introductionmentioning
confidence: 99%
“…In general, multi-agent architecture and the distribution among the intelligent devices of the control and the optimisation of the decisions may improve the energy efficiency [18]. In what follows, the field of lighting control systems will be analysed for the sake of simplicity, although the main conclusions can be extended to any other area.…”
Section: Introductionmentioning
confidence: 99%